Efficacy of Primary Stent-Graft Placement in the Treatment of Vascular Access Graft Outflow Tract Stenosis. (January 2020) - Macchi, Edoardo; Fontana, Federico; Beneventi, Alessandro; Curti, Marco; Tagliaferri, Chiara; Casamassima, Nicola; Coppola, Andrea; Piffaretti, Gabriele; Tozzi, Matteo; Genovese, Eugenio Annibale; Piacentino, Filippo
Purpose: The aim of this study is to present our personal experience using covered nitinol stent-graft in the treatment of outflow tract stenosis of arteriovenous grafts (AVGs) for hemodialysis access. Materials and Methods: Between May 2015 and October 2017, we retrospectively evaluated 36 (24 males, 12 females; mean age: 65.6 years) patients with AVGs on hemodialysis who underwent percutaneous angioplasty followed by endovascular stent-graft deployment for the treatment of stenosis of the venous outflow of the AVG. Indication for treatment included early restenosis (<3 months after previous percutaneous transluminal angioplasty [PTA]), long stenosis (stenoses >50% extending for a length >5 cm), and recoil of the stenosis after PTA performed with a noncompliant high-pressure balloon. Of 36 patients, 27 (75%) required surgical thrombectomy prior to endovascular procedure. Technical success, clinical success, primary and secondary patency, and safety were evaluated. Results: Technical success was 100%, and clinical success was 94.4%. Primary patency was 94.4%, 72.2%, 63%, 45.9%, and 45.9% at 1, 3, 6, 12, and 18 months (average: 215 days, range: 9-653 days); secondary patency was 94.4% and 86.1% at 1 and 3 months; 80.4% at 6, 12, and 18 months; and 53.6% at 24 months (average: 276.8 days, range: 9-744 days). No deaths were registered. Conclusions: In selected cases, the use of stent-graft represents an effective and safe solution for the treatment of stenotic complications of the venous outflow of AVGs, even in the setting of access thrombosis.